2016
DOI: 10.1002/anie.201602236
|View full text |Cite
|
Sign up to set email alerts
|

Organolead Halide Perovskite Nanocrystals: Branched Capping Ligands Control Crystal Size and Stability

Abstract: These are not the final page numbers! Ü Ü uniform. The low absorption/emission intensity of PNC supernatant is attributed to the low concentration of PNCs. This indicates that the as-formed PNCs can be easily collected by centrifugation (Supporting Information, Figure S5 b), which is desirable for cleaning and postprocessing in various applications.To explain the different capping effects of OA and APTES, we propose the following mechanism based on a dissolution-precipitation model (Figure 4 c). The dissolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
286
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 304 publications
(300 citation statements)
references
References 35 publications
13
286
0
1
Order By: Relevance
“…Very recently, we and others have demonstrated that the encapsulation of perovskite NCs in a polyhedral oligomeric silsesquioxane matrix or a mesoporous silica shell not only prevents this halide exchange, but also enhances the water resistivity of the NCs. [122][123][124][125] In addition, perovskite NCs are extremely sensitive and tend to degrade or transform in to other compounds (such as metallic lead) under exposure to electron beams. 25 The exact mechanisms of these transformations need to be investigated, as TEM studies are crucial for unambiguous characterization of the morphology of perovskite NCs.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, we and others have demonstrated that the encapsulation of perovskite NCs in a polyhedral oligomeric silsesquioxane matrix or a mesoporous silica shell not only prevents this halide exchange, but also enhances the water resistivity of the NCs. [122][123][124][125] In addition, perovskite NCs are extremely sensitive and tend to degrade or transform in to other compounds (such as metallic lead) under exposure to electron beams. 25 The exact mechanisms of these transformations need to be investigated, as TEM studies are crucial for unambiguous characterization of the morphology of perovskite NCs.…”
Section: Discussionmentioning
confidence: 99%
“…[6,23,31] It was found that the presence of oleic acid improves the outcome of the synthesis with amino ligands. [6,23,31] It was found that the presence of oleic acid improves the outcome of the synthesis with amino ligands.…”
Section: Synergistic Effect Between Amino and Carboxylic Functional Gmentioning
confidence: 99%
“…In addition, because of the dominant Brsurface defects in PNCs, the PL enhancement is more sensitive to the amount of R′-NH 3 + than that of R-COO -, as the former should passivate the Brdefect sites. [31] (3 of 7) 1604018 It can be seen from the PL spectra in Figure 1 that the peak position of the main emission band shifts a lot when different carboxylic acids are used, which may be due to different degrees of steric hindrance from the carboxylic capping ligands.…”
Section: Synergistic Effect Between Amino and Carboxylic Functional Gmentioning
confidence: 99%
“…Employing different ligands to improve or change the properties of as-prepared materials is a very common strategy in the colloidal QD field, and this is particularly relevant to increasing the stability of LHP NCs given their innate sensitivity to water and other polar solvents. Figure 6a shows an attempt to use different ligands other than the commonly used OA or OLA by Luo et al 97 By using branched capping ligands, (3-aminopropyl) triethoxysilane (APTES) and polyhedral oligomeric silsesquioxane (POSS) PSS-[3-(2-aminoethyl)amino]propylheptaisobutyl substituted (NH 2 -POSS), the authors showed that APTES and POSS could be used as passivators and stabilizers of MAPbBr 3 NCs. PL monitoring under exposure to ethanol under UV lamp irradiation indicated enhanced stability when using those two ligands.…”
mentioning
confidence: 99%
“…Adapted from ref (97). (b) PL of MAPbBr 3 NCs P AD–CB (in black) and P AD (in green) dispersed in toluene and in contact with water as a function of the irradiation time.…”
mentioning
confidence: 99%